Prognostic value of Linc00662/miR-16-5p/FASN in cervical cancer and regulation of tumor progression - Yu Yang; Zhanping Guo (Hereditas)
Abstract Background Cervical cancer (CC) is the world's single most frequent gynecological cancer, is more than 500,000 new annual cases globally, and is a serious threat to women's reproductive health. LncRNAs have significant effects on human diseases; nevertheless, the expression of Linc00662 in CC and its mechanism of action are not yet entirely clear. The goal of the work was to investigate the expression, prognostic value and biological utility of Linc00662 in CC progression and to identify its underlying mechanisms in molecular terms. Methods Expression levels of Linc00662, miR-16-5p and FASN in CC tissues and cells were detected through real-time quantitative PCR. Determination of cell proliferative capacity by CCK-8. Cell migration and invasion were assessed through Transwell assay. Binding of Linc00662 to miR-16-5p was mediated through a dual-luciferase reporter gene test was validated. Results Linc00662 expression levels were significantly elevated in CC. High Linc00662 expression was strongly linked to increased tumor size, later FIGO staging, poorer tumor differentiation, mesenchymal infiltration, and lymph node metastasis, and high Linc00662 expression predicted a poor prognosis. Silencing Linc00662 reduced the proliferation, migration, and invasion of CC cells. Furthermore, Linc00662 negatively regulated miR-16-5p and indirectly regulated the upregulation of FASN expression. Conclusions Linc00662 positively regulates FASN expression through targeting miR-16-5p and facilitates CC cell proliferation, migration and invasion, promoting CC progression.